OTT AND CENSORSHIP: AN ANALYTIC STUDY - Mohamed, Sumaya Abdisamad; khujumi, Illili jakha; singh, Kuldeep; sharma, Shatabdi; baruah, Anurag (IJRDO - Journal of Social Science and Humanities Research, 2022)
In the present scenario the whole world has surpass a period of long prevailed lock-down which the people around worldwide have never seen before, for such a long time. In such a boredom situation, in the era of this advance technology and the Internet, most of us like to spend their free time in front of the digital screen, where they have many options to stream. The main focus and objectives of our online research work is to find out about the reason behind the enormous rise and growth of OTT platform during the lockdown period imposed after the pandemic period of Covid-19 during 2020 summers and also to find out does certain OTT contents require censorship or not, as there is enormous increase in the nos. of subscribers for this online platform and finally the thinking of OTT platforms users about the online platforms contents and their view ships. And the final the approaches and reasons behind our research work is to understand about this needful demand of our generation i.e., main reason is that the lockdown imposed worldwide make us to shift from conventional medium to this OTT platform because of inaccessibility of movies theaters and another reason is to enjoy the entertainment life from sitting back in home and have unlimited enjoyment with the help of our finger touches. Now days most of us have the accessibility to internet which also make people to shift to the OTT platforms and this all things also make these online platforms more vulnerable to watch anywhere & by anybody.The research work was possible to come upon a certain conclusion because we have conducted the online survey with the help of some questionnaires methods which includes the different subjects thinking, knowledge and information gatherings. We have analyzed the datum of all above the subjects and came to a certain point which make us understand about the requirement of censorship for these OTT platforms.